Rural Harvested Rainwater: Effect of Roof Types and its Design on Water Quality and Health: A Case for CBP Approach in Anambra State - Akanwa, Angela Oyilieze (Review of Environment and Earth Sciences, 2020)
The rainwater quality harvested from rooftops in remote African communities has become a huge concern due to its potential risks on community health. This study addressed the effect of harvested rainwater quality and the design of the collection system from 3 common roof types on public health in Orsumoghu, Ihiala, LGA in Anambra State. This study employed the case study approach and mixed methods. Mixed methods combined the survey and laboratory methods. The survey method included field observation, interviews, photography and 250 questionnaires were randomly sampled. The laboratory method employed physic-chemical and biological analysis of rain water sampled from three (3) common rooftop systems in the area (aluminum, concrete, and zinc). The parameters analyzed were pH, temperature, hardness, conductivity, turbidity, TSS, TDS, COD, sulphates, Zinc, Lead, Cadmium and Coliform. Findings from the study showed that the poor design of RWHS coupled with mining and agricultural activities may have increased the concentration of atmospheric pollutants in the area. Findings proved that pH and three heavy metals (Zn, Ca and pb) were all above the WHO acceptable limits. Coliform as the bacterial indicator was present in the samples from aluminum and zinc roofs. However, concrete roof was free from pathogenic contamination. ANOVA analysis showed that there a difference between quality of harvested rainwater and WHO standard. To address this challenge this study recommended a community-based participatory research (CBPR) as an all-inclusive tool to promote rooftop RHW design as a rural development project that would protect the rainwater quality and minimize health risks.